Whole-Genome-Based Web Genomic Resource for Water Buffalo (Bubalus bubalis) - Khan, Aamir; Singh, Kalpana; Jaiswal, Sarika; Raza, Mustafa; Jasrotia, Rahul Singh; Kumar, Animesh; Gurjar, Anoop Kishor Singh; Kumari, Juli; Nayan, Varij; Iquebal, Mir Asif; Angadi, U. B.; Rai, Anil; et al. (Frontiers in Genetics, 2022)
Water buffalo (Bubalus bubalis), belonging to Bovidae family is economically important animal as it is the major sources of milk, meat and drought in numerous countries. It is mainly distributed in tropical and subtropical regions with global population of approximately 202 million. The advent of low cost and rapid sequencing technologies have opened a new vista for the buffalo researchers at global platform. In this study, we utilized the genomic data of five commercially important buffalo breeds, distributed globally, namely, Mediterranean, Egyptian, Bangladesh and Jaffrarabadi and Murrah. Since there is no whole genome sequence analysis of these five distinct buffalo breeds, representing highly diverse ecosystem, we made an attempt for the same. We report the first comprehensive, holistic and user-friendly web genomic resource of buffalo (BuffGR) accessible at http://backlin.cabgrid.res.in/buffgr/, that catalogues 6028881 SNPs and 613403 InDels extracted from the set of 31 buffalo tissues. We found a total of 7727122 SNPs and 634124 InDels distributed in the four breeds of buffalo (Murrah, Bangladesh, Jaffarabadi and Egyptian) with reference to Mediterranean breed. It also houses 4504691 SSR markers from all the breeds along with 1458 unique circRNAs, 37712 lncRNAs and 938 miRNAs. This comprehensive web-resource can be widely used by the buffalo researchers across the globe for use of markers in marker trait association, genetic diversity among the different breeds of buffalo, use of ncRNAs as regulatory molecules, post-transcriptional regulations, role in various diseases/ stresses. These can also be used as biomarkers to address the adulteration and traceability. This resource can also be useful in buffalo improvement programs and disease/breed management.